5x square -6x+5÷x+2 simplify
Answers
Answered by
1
Answer
x
x 2
x 2 −5x+4
x 2 −5x+4=x
x 2 −5x+4=x 2
x 2 −5x+4=x 2 −4x−x+4
x 2 −5x+4=x 2 −4x−x+4=x(x−4)−1(x−4)
x 2 −5x+4=x 2 −4x−x+4=x(x−4)−1(x−4)=(x−4)(x−1)
x 2 −5x+4=x 2 −4x−x+4=x(x−4)−1(x−4)=(x−4)(x−1)∴x
x 2 −5x+4=x 2 −4x−x+4=x(x−4)−1(x−4)=(x−4)(x−1)∴x 2
x 2 −5x+4=x 2 −4x−x+4=x(x−4)−1(x−4)=(x−4)(x−1)∴x 2 −5x+4=(x−4)(x−1)
Answered by
2
Answer:
5x√-6x+5÷x+2
Step-by-step explanation:
5x² - 6x = -x²
-x² + 5 = -6x²
6x²÷x = 6x²
6x² + 2 = 8
Similar questions